THE ANALYSIS OF PROFIT TAX FROM CONSOLIDATED GROUPS OF TAXPAYERS FOR 2012-2015 YEARS - V. Alkaeva (Вестник университета)
The article gives characteristic of consolidated group of taxpayers. The comparative analysis of profit tax from consolidated groups of taxpayers for 2012-2015 is presented. It is revealed a reduction in profit tax to the budgets of different regions of Russian Federation as a result of function of consolidated groups. Problems that led to such results are formulated.